Analisis struktur bijih mangan hasil proses sinter yang terdapat di Nagari Kiawai Kecamatan Gunung Tuleh Kabupaten Pasaman Barat (Analysis of the structure of the manganese ore resulting from the sintering process in Nagari Kiawai, Gunung Tuleh District, West Pasaman Regency) - Phobi Juwandari Putri; - Ratnawulan; - Gusnedi (PILLAR OF PHYSICS, 2015)
The Research to analyze the structure of manganese ore sinter processes occurring in the area Kiawai Sub Distric of Gunung Tuleh Regency of west Pasaman. In this research use XRF and XRD characterization tool. The results showed a transformation in the structure. Changes in the structure of the manganese ore minerals may occur as a result of warming temperatures. Structural changes that occur are tetragonal pyrolusite structure with a unit cell a = b 4.4000 Å and c = 2.8700 Å to the cubic bixbyite structure with a unit cell a = b = c = 9.4091 Å and then to the tetragonal hausmannite structure a = b = 5.7630 Å and c = 9.4560 Å. On the other hand also occur that the incorporation of bixbyite with a Rhodonite. Changes in the unit cell obtained by unit cell a = 7.6140 b = 11.8480 and c = 6.6990 the new braunite structure becomes tetragonal unit cell with  a = b = 9.4200 and c = 18 670